Observational evidence of the Kuroshio meander and its propagation in the East China Sea - Lee, SeungYong; Na, Hanna; Min, Hong Sik; Kim, Dong Guk; Nakamura, Hirohiko; Nishina, Ayako (Frontiers in Marine Science, 2025)
Entering the East China Sea (ECS) through the east of Taiwan, the Kuroshio flows northeastward, with its pathway confined along the continental slope of the Okinawa Trough. Four 75 kHz Acoustic Doppler Current Profilers (ADCPs) were deployed over a 3-year period (June 2020–June 2023), with two placed across the typical path of the Kuroshio in each of the two latitudinal bands, to examine the relationship of current variability between upstream and downstream in the ECS. The along-path and cross-path velocities from the four ADCPs show dominant intraseasonal variability with a period of 8–32 days. Within this frequency band, current velocities exhibit a strong relationship when the upstream precedes the downstream by 6 days. The amplitude of this lagged co-variability tends to be larger from May to August, with an increase in along-path speed variability of up to about 24% at approximately 250 m depth for the onshore sites and an increase in cross-path speed variability of up to about 22% within the 200–300 m layer for the offshore sites. The intraseasonal variability of the sea level anomaly associated with this observed co-variability displays the Kuroshio meanders along its path, propagating northeastward at a speed of about 14.8 km/day. These results provide observational evidence of the Kuroshio meander and its propagation in the ECS, characterized by subsurface intensification during the warm season.